HIGH ALTITUDE AND VENOUS THROMBOSIS: FREQUENCY AND RISK FACTORS - Qamar Un-Nisa Choudry (Army Medical College Rawalpindi, 2021)
Objective: To determine the effect of high altitude on frequency and risk factors of venous thrombosis in individuals ascending to high altitude